Araneofauna (Arachnida: Araneae) en cultivos de algodón (Gossypium hirsutum) transgénicos y convencionales en el norte de Santa Fe, Argentina - Soledad Almada, Melina; Sosa, María Ana; González, Alda (Revista de Biología Tropical, 2012)
Arachnofauna (Araneae: Araneae) in transgenic and conventional cotton crops (Gossypium hirsutum) in the North of Santa Fe, Argentina. Spiders have considerable potential importance for their role as predators to some pests in agricultural systems. The composition of spiders in transgenic and conventional cotton at the Research Station of INTA Reconquista (Santa Fe) was studied during the 2005-2006 season. The experiment was a complete randomized block design with three replications and three treatments: transgenic Bt cotton (ALBt), conventional cotton without chemical control (ALCSC), and conventional cotton with chemical control (ALCCC). Weekly, spiders were collected using nets, vertical cloth and pitfall-traps. A total of 1 255 specimens (16 families, and 32 species) were collected. Seven families were found in all the treatments, mainly Thomisidae (n=1 051, 84.04%) and Araneidae (n=83, 6.64%). The Hunting spiders guild ambushers (n=1 053, 83.91%), “Orb weavers” (n=85, 6.77%) and “Stalkers” (n=53, 4.22%) were more abundant. There were no sig- nificant differences in the indexes diversity between treatments. Spiders were presented during the whole crop season, with peaks about flowering and boll maturity, with the highest abundance in ALBt. This work is part of the first set of data registered in Argentina about spider’s community in cotton crops.